Energy Supply Security and Renewable Energy Policies in Turkey - Mustafa Kemal Topcu (Journal of Defense Resources Management, 2016)
As a result of Turkey’s geopolitical position and its related requirements, energy is one of the fi elds where innovation is to be speeded up. However, as a natural consequence of unplanned and incorrect energy policies, Turkey’s rate of dependency on energy has reached 72%. Since the need for energy is increasingly growing, especially as a result of the manufacturing industry in Turkey, and a large part of the consumed energy is imported, dependency seems to continue to increase. Toward this end, this article focuses on studies related to reducing external dependency on energy, while also reviewing and discussing literature survey methodology and making policy recommendations concerning energy supply security. Renewable energy has been attached great importance worldwide as well as nationwide because of providing a reliable energy source that meets economic and environmental requirements. In order to meet the increasing electricity needs of Turkey as a developing country the number on renewable energy facilities has been growing. Domestic production of equipment for renewable energy, and producing and integrating those into the conventional system are of high importance because energy supply is a security factor, sustaining reserves is a major need and reducing foreign dependency is a policy priority.